Fine-needle aspiration cytology of metaplastic carcinoma of the breast - Philip C.W. Lui (2018)
Background: Metaplastic carcinoma of the breast encompasses a heterogeneous group of tumours with variable components of sarcomatoid, squamous or poorly differentiated carcinomas. Aim: To review a series of 19 cytological preparations of metaplastic carcinomas to assess diagnostic cytological features. Methods: 17 cases of fine-needle aspirates of histologically proven metaplastic carcinomas (4 monophasic spindle cell carcinomas, 4 squamous cell carcinomas and 11 biphasic tumours) were reviewed, with an emphasis on the presence of poorly differentiated carcinoma, squamous cell carcinoma, atypical spindle cells, benign stromal fragments and necrosis. Results: All cases were diagnosed as malignant, with 68% of cases showing moderate to high cellularity, and 47% showing necrosis. If the tumours were analysed according to the constituting components histologically, 7, 15 and 8 cases, respectively, possess poorly differentiated carcinoma cells, sarcomatoid malignant cells and squamous carcinoma cells, whereas these components were cytologically identified in 11, 10 and 7 cases, respectively. Dual tumour populations were identified in only 5 of the 11 biphasic carcinomas in the cytological preparations; and the stromal material was cytologically identified in the only case with chondroid stroma. Conclusions: Identification of metaplastic carcinoma in cytology remains problematic. There seems to be morphological overlap between various components. The identification of dual components, unequivocal squamous carcinoma cells and chondroid stroma is helpful for diagnosis, but it is uncommon. The presence of poorly differentiated carcinoma cells with a suggestion of focal spindle morphology is another clue to the suggestion of metaplastic carcinoma.